INTERNATIONAL LEGAL MECHANISMS FOR ADVANCING WOMEN’S RIGHTS IN ISLAMIC STATES: THE ROLE OF GLOBAL AND REGIONAL INSTITUTIONS - TAYLOR, ALLA (Ehrlich's Journal, 2025)
This article examines the role of international and regional institutions in development of women’s rights in Islamic states, focusing on the effectiveness of legal instruments and the challenges associated with their enforcement. The research highlights the contributions of the United Nations (UN), UN Women, the Organization of Islamic Cooperation (OIC), the League of Arab States (LAS), and African regional institutions, analyzing their strategies, legal frameworks, and policies aimed at advocating women’s rights in Islamic societies. The promotion and protection of women’s rights within Islamic states have been a subject of growing importance in international law, especially the intersection of global human rights norms and Islamic legal traditions. It was found that the international treaties such as the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) and regional legal frameworks provide mechanisms for advancing gender equality and women’s rights empowerment, but their implementation remains complex due to historical traditions, cultural norms, and religious interpretations. Some states have made significant progress in legal reforms, particularly in areas such as education, economic participation, and political engagement, but we can observe that many challenges still exist. These include reservations to international treaties, weak enforcement mechanisms, and socio-cultural barriers that limit women’s full legal autonomy. We can see the role of regional organizations is particularly critical. Institutions like the OIC and LAS aim to balance human rights obligations with religious and cultural considerations. However, the effectiveness of these organizations is often hindered by their non-binding resolutions and the varying levels of commitment from member states. The findings indicate that international and regional institutions have contributed to raising awareness and fostering legal reforms, but significant gaps remain in implementation. It was found that there is a need for a context-sensitive approach that respects cultural and religious values but at the same time improving legal protections for women. Developing institutional frameworks, increasing advocacy efforts, and promoting legal education are important steps toward ensuring greater gender equality in Islamic legal systems.